Message to President Clinton
The tape includes 5 different topic such as a message to President Clinton by an American of Serbian origin, and a Serbian women talk about being raped and tortured by Croats, and Josanica massacre victims talk about the killings. At the end in the report "What do Albanians want?", a Belgrade Law Professor Budimir Kosutic talks about history behind the conflict in Kosovo.